Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
3 Answers
- OutlierLv 42 years agoFavorite Answer
(i) (a - 1)^3 - 8 + (a + 1)^3 + 6(a^2 - 1)
= (a - 1)^3 + (a + 1)^3 - 8 + 6(a^2 - 1)
First, recognize that a^2 - 1 = a^2 - 1^2 = (a - 1) (a + 1), since it is a difference of two squares. Recall that x^2 - y^2 = (x - y) (x + y)
Also note that (a +1)^3 - 8 = (a + 1)^3 - 2^3 = (a + 1 - 2) [(a + 1)^2 + (a + 1) (2) + 2^2], since it is a difference of two cubes. Recall that x^3 - y^3 = (x - y) [x^2 + xy + y^2]
So we have (a +1)^3 - 8 = (a - 1) [(a + 1)^2 + 2 (a +1) + 4]
Therefore,
(a - 1)^3 - 8 + (a + 1)^3 + 6(a^2 - 1)
= (a - 1)^3 + (a - 1) [(a + 1)^2 + 2 (a +1) + 4] + 6 (a - 1) (a + 1)
Note that (a - 1) is a common factor for all terms, so we have
(a - 1) [(a - 1)^2 + (a + 1)^2 + 2 (a + 1) + 4 + 6(a + 1)]
= (a - 1) [(a^2 - 2a + 1 + a^2 + 2a + 1 + 2a + 2 + 4 + 6a + 6]
= (a - 1) [2a^2 + 8a + 14]
= 2 (a - 1) (a^2 + 4a + 7)
(ii) x^2 - y^2 - 2z^2 + zx + 3yz
= -2z^2 + zx + 3yz + x^2 - y^2
= z (-2z + x + 3y) + x^2 - y^2
= z (x + 3y - 2z) + (x - y) (x + y)
Alternatively,
Note that (x - y + 2z) (x + y - z) = x^2 + xy - xz - xy - y^2 + yz - 2xz + 2yz - 2z^2
= x^2 - y^2 - 2z^2 - 3xz + 3yz
So x^2 - y^2 - 2z^2 + zx + 3yz = (x - y + 2z) (x + y - z) + 4xz
- ?Lv 72 years ago
(i)
(a - 1)^3 - 8 + (a + 1)^3 + 6(a² - 1)
= 2 (a - 1) (a^2 + 4 a + 7)
(ii)
x² - y² - 2z² + zx + 3yz
= (x + y - z) (x - y + 2 z)
- la consoleLv 72 years ago
= (a - 1)³ - 8 + (a + 1)³ + 6.(a² - 1)
= (a - 1)².(a - 1) - 8 + (a + 1)².(a + 1) + 6a² - 6
= (a² - 2a + 1).(a - 1) - 8 + (a² + 2a + 1).(a + 1) + 6a² - 6
= a³ - a² - 2a² + 2a + a - 1 - 8 + a³ + a² + 2a² + 2a + a + 1 + 6a² - 6
= 2a³ + 6a² + 6a - 14
= 2a³ + (8a² - 2a²) + (14a - 8a) - 14
= 2a³ + 8a² - 2a² + 14a - 8a - 14
= 2a³ + 8a² + 14a - 2a² - 8a - 14
= (2a³ + 8a² + 14a) - (2a² + 8a + 14)
= a.(2a² + 8a + 14) - (2a² + 8a + 14)
= (a - 1).(2a² + 8a + 14)
= 2.(a - 1).(a² + 4a + 7)